The Effect of Arm Muscle Training on Back Hand Strokes in Court Tennis - Ahmad Faisal Waruhu; Nurkadri; Ronaldo Sagala; Adam Yusril Mahendra; Kriswandoyo; Laurencia Averina (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aimed to explore the role played by arm muscle exercises in improving the strength and accuracy of strokes in court tennis players. In the highly competitive world of tennis, having optimal physical strength and the ability to control shots is a key success factor. The study used a combined approach, including surveys, physical measurements, and statistical analysis. We observed a group of court tennis players who followed a leg muscle training program over a period of time, while the other group did not do that particular exercise. The participants were tested for arm muscle strength, then they were asked to play in situations that simulated an actual court tennis match. The results of this study revealed that players who underwent an arm muscle training program consistently experienced a significant increase in arm muscle strength. In addition, they also show an increase in their ability to better control and direct their punches, resulting in stronger and more targeted punches. These findings provide strong support for the importance of arm muscle exercises in improving the performance of court tennis players.